Analisis Metakognitif Dalam Memecahkan Masalah Pada Materi Hukum Termodinamika Kelas XI SMAN 1 Tambang - Catharine Miranda; Muhammad Nasir; M. Rahmad (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
Metacognitive is the ability that a student has how measures or control his mindset, knowledge about his knowledge, and skills to analyze the product and learning outcomes. If students have good metacognitive, it will be more effective to select and find important information to solve problems than students who don’t have metacognitive. Swartz and Perkins divide the metacognitive level into 4 parts, namely tacit use, aware use, strategic use, and reflective use. This study aims to describe the metacognitive levels of students who have high, medium and low abilities in solving problems in the Law of Thermodynamics material. This research was conducted at SMA Negeri 1 Tambang with 23 students from class XI MIPA 2 as research subjects. This research was included in a descriptive study. The written test is a data collection method used in this study. The results of the test will be used to analyze students' metacognitive abilities. The results of this study are students who have learning outcomes in high groups are at the level of metacognitive Reflective Use. Students who have learning outcomes in groups are at the Strategic Use metacognitive level. Students who have low group learning outcomes are at the Tacid Use metacognitive level.